173k views
0 votes
Hey any oneill give brainleast please help me

Hey any oneill give brainleast please help me-example-1

2 Answers

6 votes

Answer:

8

Explanation:

User Dan Saltmer
by
4.3k points
2 votes

Answer:

8

Explanation:

So we have the expression:


(-(11)/(2)x+3)-2(-(11)/(4)x-(5)/(2))

First, distribute the right:


=(-(11)/(2)x+3)+((11)/(2)x+5)

Combine like terms:


=(-(11)/(2)x+(11)/(2)x)+(3+5)

The fractions will cancel:


=3+5

Add:


=8

Our answer is 8 :)

User Btimby
by
4.9k points